KEBIJAKAN PEMANFAATAN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) DI SATLANTAS SUKOHARJO - Aditya Pratama, Sadam Ridho; Prasetiyo, Wibowo Heru; Setyadi, Yulianto Bambang (Universitas Muhammadiyah Ponorogo, 2023)
This study seeks to determine the policy regarding using Electronic Traffic Law Enforcement (ETLE) to maintain and enhance traffic orders. ETLE is based on Law (UU) Number 22 of 2009 concerning Road Traffic and Transportation and Government Regulation (PP) Number 80 of 2012 concerning Procedures for Inspecting Motorized Vehicles on the Road and Enforcement of Traffic and Road Transportation Violations. From October 2022 to February 2023, this research was conducted at the state police of the Republic of Indonesia in Central Java Resor Sukoharjo. To observe and comprehend the subjects and objects of study, the researcher employs a qualitative descriptive method based on observations made in the field. During and after data collection, data collection techniques, such as observation, interviews, and documentation, are combined with data analysis, which includes data reduction, data presentation, and conclusion or verification drawing. As evidenced by the recapitulation of 16,538 violation cases in Sukoharjo, the results demonstrated the public's need for more understanding regarding electronic fines and discipline in maintaining driving order must be improved. Additional socialization efforts are required to maintain traffic order and reduce instances of these violations. Replacing conventional ticketing with electronic ticketing, or ETLE, will result in more equitable, transparent, and efficient public services. To support security, order, safety, and order in traffic, the benefits can be felt by all levels of society simultaneously.